Conflict Mitigation Strategies in Housing And Settlement Development Projects: A Case Study Of Indonesia's New National Capital City (IKN) - Imsaskia Cassandra (Journal of Architecture & Environment, 2024)
This study aims to highlight the conflict, especially those occurring in housing and settlement development projects, and provide relevant solutions to enhance project efficiency in New National Capital City (IKN), Indonesia. Site management involves a series of operations that combine various materials to achieve the final construction result. Therefore, to improve project productivity, it is essential to identify and implement key management techniques. Critical components of project execution and on-site management include integration management, site planning, resource management, site safety, monitoring, and supervision. Neglecting these components can lead to decreased productivity. Thus, addressing these issues and recognizing these components and tensions is essential. The study utilizes literature review, on-site observations, and semi structured interviews during the execution of construction projects. These conflicts were analyzed using factor analysis based on the average ranking obtained through questionnaire surveys. Data was collected from 48 respondents, selected based on simple random sampling from construction stakeholders. Feedback from the respondents was analyzed using the frequency for ranking purposes. The results identified seven main conflict factors. This aims to assist in conflict management in upcoming projects.